PEMBERITAAN MEDIA TEKNOPOLITIK KEBIJAKAN SMART FARMING DI INDONESIA - Sanjaya, Andika; Setyawan, Sidiq; Nugraha, Agustia Landra (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2026)
Smart farming is an ambitious concept to strengthen food security and eradicate hunger at the national and global levels. Technological innovation offers agricultural efficiency, increases crop productivity, and attracts the interest of a new generation of young farmers. Technology is not a panacea to overcome the decline of Indonesia's agricultural sector. Smart farming requires cross- stakeholder collaboration to achieve government goals. Media, with its reporting, is a key collaborator in smart farming policies. This qualitative content analysis study aims to explain how online media reports on smart farming. Similar to smart cities, smart farming can be a solution or just a false label. Research findings indicate a lack of mainstream online media coverage and the importance of cross- media stakeholder collaboration. The government still plays the most significant role with a Java- centric approach to manage media reporting of smart farming ecosystem. Issues of productivity, food security, and aging farmers are the goals of smart farming.